Marketing Strategis For Hotel Mangkuto, Payakumbuh. - Winda, Trimela; Paramarta, Riawan B (The Indonesian Journal of Business Administration, 2015)
Abstract- Currently hospitality business in Indonesia is growing along with the increasing spotlight on tourism. Hotel is a company engaged in the service that provides services to stay, meeting room, food or beverages, and more. All hotels want a high occupancy rate, but this cannot be separated from what is used in strategy for each hotel. The business issues in this final project is occupancy rates are currently only 47% of which have not yet reached the target standard STR Global hotel indonesia is 69.4%.The methodology used is the analysis of the marketing mix 7P, Servqual, brand equity. The analysis was performed through the data obtained from the questionnaire that consists of the data respondent, brand awareness, brand image, perceived quality, promotion, and brand loyalty. All questionnaires filled out by the customer Mangkuto except the brand awareness that filled by the customer Payakumbuh Mangkuto and people around payakumbuh. From the results of the questionnaire, found the problem in terms of service, brand image, and promotion. For this service, the problem in terms of professional employees and the response given to customers still unsatisfactory. For the image of the brand, there are problems such as incomplete facilities and the price is not affordable. For promotion, the hotel is lack of utilization such as media social, advertising, and events.The proposed solution is mangkuto should increase promotion using social media, event sponsorships, and advertising. In addition, repair facilities and provide attractive discounts for hotel customers. Improve service by way of renovating the meeting room, check the cleanliness of the rooms and meeting rooms, providing appropriate equipment in meetings, increasing the number of variety of food, improve service employees. The solutions are applied in the implementation plan. The implementation plan consists of objectives, activities, indicators, targets, resources, responsible, and timeline.Keywords: marketing mix, servqual, brand equity, brand awareness, brand image, perceived quality, promotion, and brand loyalty.Ã‚Â